Mobilitas penduduk dan risiko penularan HIV & AIDS: Kasus di Provinsi Bali - Purwaningsih, Sri Sunarti (Jurnal Kependudukan Indonesia, 2013)
Bali is a well-known tourist destination, since the Dutch colonial time. Since then, many people from outside Bali come and go to Bali as tourist. As a result Balinese people are interacting with people from various demographic and cultural backgrounds. This interaction has both positive and negative consequences. In-migration and tourism has benefited the local economy but has also changed peoples life style. Since it was found in Bali 1987, HIV & AIDS cases in this region grow fastly and spread out to all over districts in Bali. This indicated that people in Bali are at risk when it comes to sexual transmitted diseases including HIV & AIDS. Our study in 1999 found that HIV was becoming a phenomenon amongst young people especially beach-boys. They thought that sexual relations with foreigners were not risky as they were convinced that foreigners were free from HIV. This paper analyse some issues in relation to migration and the HIV & AIDS phenomenon. Amongst others the paper discuss the relation between the mobility of the population and the negative impacts on people lives such as HIV AIDS. Finally, the paper discuss local knowledge that can be used to prevent the transition of HIV.